2013
DOI: 10.1371/journal.pone.0079259
|View full text |Cite
|
Sign up to set email alerts
|

Novel B19-Like Parvovirus in the Brain of a Harbor Seal

Abstract: Using random PCR in combination with next-generation sequencing, a novel parvovirus was detected in the brain of a young harbor seal (Phoca vitulina) with chronic non-suppurative meningo-encephalitis that was rehabilitated at the Seal Rehabilitation and Research Centre (SRRC) in the Netherlands. In addition, two novel viruses belonging to the family Anelloviridae were detected in the lungs of this animal. Phylogenetic analysis of the coding sequence of the novel parvovirus, tentatively called Seal parvovirus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 40 publications
4
24
0
2
Order By: Relevance
“…Of those nine samples, two were collected from harbor seals that had died during the 1988 and seven during the 2002 PDV outbreaks (six harbor seals and one grey seal). Combination of the data obtained in the present study with data from a previous study [12], resulted in a SePV prevalence in spleen samples of 6.9% for harbor seals (based on in total 174 animals) and 9.1% for grey seals (n = 11) ( Figure S1, Table 1 ). …”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…Of those nine samples, two were collected from harbor seals that had died during the 1988 and seven during the 2002 PDV outbreaks (six harbor seals and one grey seal). Combination of the data obtained in the present study with data from a previous study [12], resulted in a SePV prevalence in spleen samples of 6.9% for harbor seals (based on in total 174 animals) and 9.1% for grey seals (n = 11) ( Figure S1, Table 1 ). …”
Section: Resultssupporting
confidence: 66%
“…SePV was discovered in 2012 in a young harbor seal with severe chronic meningo-encephalitis [12]. In the present study, we demonstrated that SePV was already circulating among both harbor and grey seals of Northwestern Europe since 1988, although SePV was detected only in a relatively small number of samples.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…In 2007, it was reported that only 56% of marine mammal mortality events had a known cause of death (Gulland & Hall, 2007), leaving the pathogens and physiological causes of many diseases to be discovered. However, the introduction of high-throughput sequencing (HTS) has led to the identification of many more marine mammal pathogens, such as seal and California sea lion anellovirus, phocine herpesvirus 7, and seal parvovirus (Ng et al, 2009; Ng et al, 2011; Bodewes et al, 2013; Kuiken et al, 2015). Therefore, the combination of stranded animals and HTS are vital resources for the discovery of marine mammal diseases.…”
Section: Introductionmentioning
confidence: 99%